Effect of primary crystallite size on the high-rate performance of Li4Ti5O12 microspheres. (10th July 2016) - Zhao, Shuo; Ka, Ou; Xian, Xiaochao; Sun, Leiming; Wang, Jing
Graphical abstract: Abstract: Monodisperse Li4 Ti5 O12 (LTO) microspheres with different primary crystallite sizes were synthesized using the same cetyltrimethylammonium bromide-assisted hydrothermal method but different post-calcination temperatures (600 and 700 °C). The two different LTO microspheres have the same diameter about 4 μm, but smaller primary crystallite size and higher surface area are obtained at 600 °C (LTO600). The specific capacities at 0.1C are both close to the theoretical capacity of LTO for the two samples; higher specific capacity is obtained with LTO600 at high C-rate, indicating beneficial effect of smaller primary crystallite size and larger surface area. Notably, LTO600 exhibits superior rate performance and excellent cyclic stability. The charge specific capacities at 5C, 10C, 20C and 50C are up to 158, 154, 153 and 148 mAh g −1, respectively. More importantly, the capacity retention after 400 cycles at 5C is as high as 150 mAh g −1 .